Exploitation of Antarctic resources [microform] : hearing before the Subcommittee on Arms Control, Oceans, and International Environment of the Committee on Foreign Relations, United States Senate, Ninety-fifth Congress, second session . February 6, 1978. - United States. Congress. Senate. Committee on Foreign Relations. Subcommittee on Arms Control, Oceans, and International Environment. (Washington : U.S. Govt. Print. Off., 1978)
Reuse of record except for individual research requires license from Congressional Information Service, Inc. CIS Microfiche Accession Numbers: CIS 78 S381-18 Includes bibliographical references. Microfiche. Mode of access: Internet.